Blended Learning Environment: An Approach To Enhance Students’s Learning Experiences Outside School - Coll, Sandhya Devi; Treagust, David (2017)
This paper reports on blended learning environment approach to help enhance students’ learning out comes in science during Learning Experiences Outside School (LEOS). This inquiry took the nature of an ethnographic case study (Lincoln & Guba 1985; Merriam, 1988), and sought to establish ways of enhancing students’ LEOS. The context of the inquiry was a private rural religious secondary school in New Zealand. The New Zealand Science Curriculum is based on a constructivist-based view of learning which provides opportunities for a number of possible learning experiences for science, including LEOS, to enrich student experiences, motivate them to learn science, encourage life-long learning, and provide exposure to future careers (Hofstein & Rosenfeld,1996; Tal, 2012). However, to make the most of these learning experiences outside the school, it is important that adequate preparation is done, before, during and after these visits. Sadly, the last two decades of research suggest that activities outside school such as field trips have not necessarily been used as a means to improveschool-basedlearning (Rennie & McClafferty, 1996). This inquiry utilised an integrated online learning model, using Moodle, as a means to increase student collaboration and communication where students become self-directed, negotiate their own goals, express meaningful ideas and display a strong sense of collective ownership (Scanlon, Jones & Waycott, 2005; Willett, 2007). The digital space provided by Moodle allows students significant autonomy which encourages social interactions and this promotes learning and social construction of knowledge (Brown, Collins, & Duguid, 1989; Lewin, 2004).